2017
DOI: 10.1523/jneurosci.1277-17.2017
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Two Classes of Somatosensory Neurons That Display Resistance to Retrograde Infection by Rabies Virus

Abstract: Glycoprotein-deleted rabies virus-mediated monosynaptic tracing has become a standard method for neuronal circuit mapping, and is applied to virtually all parts of the rodent nervous system, including the spinal cord and primary sensory neurons. Here we identified two classes of unmyelinated sensory neurons (nonpeptidergic and C-fiber low-threshold mechanoreceptor neurons) resistant to direct and trans-synaptic infection from the spinal cord with rabies viruses that carry glycoproteins in their envelopes and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 43 publications
2
35
0
Order By: Relevance
“…The remainder may include contributions from other classes of primary afferent (e.g. myelinated LTMRs 21 , thermoreceptors or those that express MrgB4 52 ) as well as from descending sources such as the corticospinal tract 27 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The remainder may include contributions from other classes of primary afferent (e.g. myelinated LTMRs 21 , thermoreceptors or those that express MrgB4 52 ) as well as from descending sources such as the corticospinal tract 27 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, mice lacking GRPR, or those in which GRPR-expressing dorsal horn neurons are ablated, show reduced responses in several itch models 7 , 8 , 12 , 13 . Excitatory interneurons within the SDH provide a source of GRP 7 , 14 16 , and several studies have investigated the role of these cells by using BAC transgenic mouse lines from the GENSAT project 17 in which either enhanced green fluorescent protein (eGFP) 7 , 14 , 15 , 18 20 or Cre recombinase 18 21 is expressed under control of the Grp promoter (GRP::eGFP and GRP::Cre, respectively). We have reported that the eGFP-positive cells in the GRP::eGFP line are all excitatory, accounting for ~ 15% of the excitatory interneurons in laminae I-II 4 , 14 , and that they are largely separate from populations defined by the expression of five other peptides: cholecystokinin (CCK), neurotensin, neurokinin B (NKB), neuropeptide FF (NPFF) and substance P (SP) 3 , 4 , 22 , 23 .…”
Section: Introductionmentioning
confidence: 99%
“…To date, sensory dorsal root ganglia (DRG) or ventral spinal cord neurons have been used for RABV axonal transport studies. However, unlike SCG, spinal cord neurons exhibit limited axonal projections in compartmented cultures [ 12 ], and DRG are heterogenous with subpopulations of unmyelinated neurons that display resistance to RABV infection [ 38 ]. We established an ex vivo model of RABV infection in compartmented SCG neurons to facilitate high resolution imaging of RABV axon transport as well as concurrent biochemical analyses of RABV-infected axons.…”
Section: Discussionmentioning
confidence: 99%
“…Intraspinal virus injections were made in isoflurane-anesthetized mice using a motorized stereotaxic frame (David Kopf Instruments and Neurostar). Three separate unilateral injections of 300 nl each were performed at a depth of 300 m using glass micropipettes connected to a PHD ultra nanomite syringe pump (Harvard Apparatus) as described previously (Albisetti et al, 2017;Haenraets et al, 2018). The following viruses were used: for chemogenetic activation, AAV1.hSyn.flex.…”
Section: Methodsmentioning
confidence: 99%